Very efficient composite titania membranes in hybrid ultrafiltration/photocatalysis water treatment processes - Athanasekou, C.P.; Romanos, G.E.; Katsaros, F.K.; Kordatos, K.; V. Likodimos; P. Falaras (Journal of Membrane Science, 2012)
Composite TiO 2 photocatalytic ultrafiltration (UF) membranes were developed through chemical vapour layer-by-layer deposition (LBL/CVD) of TiO 2. The technique comprised chemisorption or physisorption of the titanium isopropoxide (TTIP) vapour and a subsequent oxidative treatment in order to promote the precursor condensation and generate new adsorption sites for the accomplishment of the successive adsorption/surface reaction steps. Both membrane sides were covered with TiO 2 photocatalyst without affecting the high water recovery efficiency. For reasons of comparison, one of the membranes was prepared through TiO 2 nanoparticle growth (NPG/CVD), a procedure extensively studied in a previous work of our group. The membrane efficiency in photo degradation of methyl orange was evaluated in an innovative continuous flow reactor, applying UV irradiation on the annular and bore surfaces. The membranes developed through the physisorption path were highly efficient in the decomposition of azo-dye pollutant, exhibiting low adsorption-fouling tendency and high water permeability. © 2011 Elsevier B.V.